The Legal Effectiveness of Application of E-Tiring (E-Tilang) Methods in Criminal Enforcement of Traffic Violations - Rustam Rustam; Latifah Hanim; R. Sugiharto Sugiharto (Law Development Journal, 2022)
This research aims to analyze the juridical substance of formulative policies for traffic violations criminal law enforcement using E-Tiring. This research used a normative juridical method with research specifications in the form of descriptive analysis. Based on the discussion, it was concluded that the arrangement of infrastructure or the arrangement of the governance system for handling traffic violations based on technology and the National Police Grand Strategy 2005-2025 policy (Public Trust Building, Partnership Building, and Strive For Excellence) which was strengthened by the 2015-2019 Police Strategic Plan which includes among others: First, the fulfillment of the Alpalkam/Almatsus Polri to support strengthening the main tasks and functions of the National Police. Second, the establishment of a professional, moral, modern and superior Polri posture through changing the mindset and culture set. Third, development of police technology and information systems in a sustainable manner that is integrated through research and scientific studies to support optimal Polri performance. The National Police has made various efforts to improve performance standards in a sustainable manner by rolling out creative breakthroughs and service systems in line with the current National Police Strategic Plan, particularly in the implementation of handling violations through the E-Tiring system.